Operation of Battery Storage Systems in Auxiliary Services and Balancing Markets in the Electricity Market - Mammadov, Tahir (ADA University, 2024)
The battery storage systems (BSS) will be an integral part of solving the challenges caused by increasing the penetration of renewable energy sources into modern grids. In this respect, these systems will stabilize the grid not only in frequency and voltage fluctuations but also increase energy reliability and economic efficiency. The present work puts its focus on the integration of BSS in standalone and grid-connected PV systems, covering its design, operation characteristics, and economic impacts of such integration. Advanced simulation tools like PVsyst are being used in investigating and optimizing systems through load profiles and meteorological conditions, including specifications that concern the equipment. The present research has found out the functions of BSS in allowing resilience and flexibility of the grids. With the help of BSS, stand-alone systems ensure that the power supply remains continuous in conditions of low solar irradiance, and for those using gridconnected systems, these ensure energy management efficiency with the purpose of peak shaving. BSS applications are far broader than energy storage and include issues like frequency and voltage regulation, improving grid resilience through blackouts, and economic advantage in terms of peak shaving and arbitrage; they have numerous applications and implications within current power systems. The key findings have proved that lithium-ion batteries, due to their high energy density, fast response, and declining prices, are the most suitable for BSS applications. Besides this, the inclusion of tracking systems and optimized PV array orientations enhances energy capture efficiency. The study also covers the latest developments in other battery technologies, such as solid-state and sodium-ion batteries, which have demonstrated the potential to overcome cost and efficiency barriers. Economic analysis underlines the viability of BSS in both stand-alone and gridconnected configurations, while life-cycle cost analyses have shown that these systems are cost-effective in the long term. The environmental benefits are reflected in reduced carbon emissions and increased renewable energy use. Challenges include battery degradation, high upfront costs, and regulatory barriers. Scaling up BSS adoption will require addressing these challenges through policy support, technology advancement, and innovative system designs.This study adds to the growing knowledge in the integration of renewable energy, and from the results, it gives actionable recommendations to improve system performance, further cost-efficiency, and sustainability. The findings highlight the potential transformation of BSS to shape the future of energy systems by paving the way for an energy transition that is both sustainable and resilient.
Keywords: Battery storage systems -- Economic aspects; Photovoltaic power generation -- Storage; Solar power systems -- Energy efficiency; Renewable energy sources -- Integration; IT and Engineering